The SWIFT Affair - Johannes Köppel (Graduate Institute Publications, 2011)
The story broke in 2006: Since 9/11, US intelligence services have had access to practically any international money transfer data by infiltrating the SWIFT (Society for Worldwide Interbank Financial Telecommunication) network. Banks worldwide transfer money orders and personal customer data through this network. While the surveillance was all-embracing in 2001, it was gradually limited over the course of the last few years. Revealed by the New York Times, the SWIFT affair has had global as w...